Measurement of uranium isotope ratios in Fukushima-accident contaminated soil samples using multi collector inductively coupled plasma mass spectrometry. (June 2021) - Murugan, R.; Kavasi, N.; Sahoo, S.K.; Omori, Y.; Sorimachi, A.; Takahashi, H.; Aono, T.
Abstract: In the present study, 137 Cs and 238 U activity concentrations, 234 U/ 238 U activity ratio, and 235 U/ 238 U isotope ratio were measured in fifteen soil samples collected from the exclusion zone around the Fukushima Daiichi Nuclear Power Station (FDNPS). The 137 Cs activity concentrations of Fukushima-accident contaminated soil samples ranged from 29.9 to 4780 kBq kg −1 with a mean of 2007 kBq kg −1 . On the other hand, the 238 U activity concentrations of these soil samples ranged from 5.2 to 22.4 Bq kg −1 with a mean of 13.2 Bq kg −1 . The activity ratios of 234 U/ 238 U ranged from 0.973 to 1.023. The 235 U/ 238 U isotope ratios of these exclusion zone soil samples varied from 0.007246 to 0.007260, and they were similar to the natural terrestrial ratio confirming the natural origin. Using isotope dilution technique, the 235 U/ 137 Cs activity ratio was theoretically estimated for highly 137 Cs contaminated soil samples from Fukushima exclusion zone ranged from 5.01 × 10 −8 - 6.16 × 10 −7 with a mean value of 2.51 × 10 −7 . Highlights: 137 Cs activity concentration ranged from 29.9 to 4780 kBq kg −1 . The activity ratio of 234 U/ 238 U were in the range of 0.973–1.023. The 235 U/ 238 U isotope ratios indicate natural in origin for Fukushima soil samples. The 235 U/ 137 Cs activity ratio ranged from 5.01 × 10 −8 - 6.16 × 10 −7 for Fukushima exclusion zone soil samples.